Age structure of sitophilus oryzae using fragrant rice, basmati rice, brown rice and local white rice / Muhamad Ridzuan Rosli - Rosli, Muhamad Ridzuan (2020)
Stored product insect cause more than one fifth of total damages in rice in developing countries commonly and one of the insect that contributes to this problem is rice weevil Sitophilus oryzae. The huge amount of loss could be associated with their biology because their all four larval stage and pupal stage occured inside the grain. Hence causing their control and elimination are very difficult .Thus this thesis focuses on the rice weevil S. oryzae age structure relationship with morphological characteristics based on the amount of nutrient used which might gain information on the preference and development of rice weevil S. oryzae. Through that, a new process can be developed later to protect the food grain in a better way. The tests were conducting by rearing this species in the four types of rice and were measured according to their age. Rice weevil S. oryzae were exposed to fragrant rice, basmati rice, brown rice and local white rice. Results shows there is no significant difference between each type of rice, particularly on the 1st until 28th day range. However, the growth development of rice weevil S. oryzae are correlated with the types of nutrient used in this study. It is found that rice weevil S. oryzae which that reared in brown rice shows the fastest growth development compared to the other type of rice.